Indoor air quality in a preschool - Koruba, Dorota; Zender-Świercz, Ewa; Piotrowski, Jerzy; Orman, Łukasz; Telejko, Marek (Budownictwo i Architektura / Civil and Architectural Engineering, 2014)
The article demonstrates the results of research on the indoor air quality (IAQ) in one of chosen preschools. In such facilities, the standard solution is a system of natural ventilation. Only a small percentage of such buildings is equipped with a mechanical ventilation system with adjustable parameters of the microclimate. The article presents the results of indoor air quality in the local preschool located in Kielce. In the present facility natural ventilation system was used. Preliminary studies confirmed the poor quality of indoor air in a subjected building. During the study, two improvements aimed at improving air quality were proposed. The first improvement was to increase the supply air stream. The second one concerned the installation of equipment for the treatment of indoor air. The results indicate that under certain guidelines it is possible to improve indoor air quality. As an indicator of indoor air quality, concentration of carbon dioxide was adopted. In addition, microbiological tests were performed indoors.